Pengaruh Suplementasi Daun Sengon (Albazia falcataria) Terhadap Kecernaan dan Fermentabilitas Bagasse Hasil Amoniasi Secara In Vitro - Suryadi, Suryadi (Fakultas Peternakan Universitas Jambi, 2008)
The objective of the research was to study the influence of sengon leaf supplementation on the digestibility and fermentability of urea treated bagasse using with in vitro technique. The matter were used in the research was the bagasse-urea treated which had good degradation characteristic which origin from the first research. Completely randomized design with five treatments of 0%, 5%, 10%, 15% and 20% sengon leaf supplementation and four replications were used in this experiments. Parameter measured were the dry metter and organic matter digestibility, acidity degree, ammonia (N-NH3) and VFA production of in vitro test. The result showed that the sengon leaf supplementation was significant effect (P>0.05) on the digestibility and fermentability bagasse-urea treated with in vitro technique. It could be concluded that bagasse treated of 6% urea solution that used in the second step research could be increased their digestibility and fermentability by supplementation of 10% sengon leaf.